The Effect of Hatha Yoga and Namaskar Surya Yoga on Flexibility and Balance in Women - Normi Prihantia Bintari; Noortje Anita; Soni Sulistyarto (BIRCU, 2021)
The purpose of this study was to analyze the effect of Hatha yoga and Surya Namaskar yoga on flexibility and balance in women. The research method used in this research is quantitative with quasi-experimental method, with research design using pretest and posttest, group I Hatha Yoga, group II Yoga Surya Namaskar and group III control group, with data analysis using ANOVA. The data collection process was carried out by testing the flexibility and balance of the FIT FUN PLACE exercise group. Then the data were analyzed using the SPSS series, the target of this research was members of the FIT FUN PLACE gymnastics with 30 members, divided into 3 groups of 10 people each, this study was conducted for 16 meetings. There is a significant effect on increasing flexibility in the group that does Hatha Yoga with an average increase in flexibility of 2.9 or an increase of 9%. A significant effect on improving balance in the group that did Hatha with an average increase in balance of 2.77 or 13%. Increased flexibility in the group who did Surya Nakasmara Yoga with an average increase in flexibility of 2.35 or an increase of 7%. Improved balance in the group that did Surya Nakasmara Yoga with an average increase in balance of 4.56 or an increase of 19%.